Zagadnienia Kołowo-Symetryczne Płaskich Siatek O Symetrii Środkowej - Zieliński, S. (Engineering Transactions, 1967)
The present paper gives some solutions for centrally symmetric bar lattices (a polar lattice, in particular). The considerations are done in polar coordinates. In the case of an axially symmetric load the only unknown geometrical quantity is the radial displacement wr. It is shown that for an axially symmetric load there are no moment stresses 〖m^α〗^3= 0, not only for polar lattices but also for centrally symmetric lattices under consideration. The components of the affine tensor of elastic rigidity A are calculated for a number of lattice-types. The inverse method, by imposing the form of the displacement function wr, is used to obtain the conditions to be satisfied by the lattice structure. The solutions for the lattice types under consideration are obtained in the form of power series.